2011
DOI: 10.1177/0037549711413001
|View full text |Cite
|
Sign up to set email alerts
|

Discrete event modeling and massively parallel execution of epidemic outbreak phenomena

Abstract: In complex phenomena such as epidemiological outbreaks, the intensity of inherent feedback effects and the significant role of transients in the dynamics make simulation the only effective method for proactive, reactive or post facto analysis. The spatial scale, runtime speed, and behavioral detail needed in detailed simulations of epidemic outbreaks cannot be supported by sequential or small-scale parallel execution, making it necessary to use large-scale parallel processing. Here, an optimistic parallel exec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…The use of ABMs with explicit agent mobility distinguishes the proposed research from work from those reported by Barrett et al [1], Bisset et al [2], and Perumalla et al [19]. These three investigations use a reaction-diffusion approach involving contact graphs for epidemic modeling.…”
Section: Related Researchmentioning
confidence: 97%
“…The use of ABMs with explicit agent mobility distinguishes the proposed research from work from those reported by Barrett et al [1], Bisset et al [2], and Perumalla et al [19]. These three investigations use a reaction-diffusion approach involving contact graphs for epidemic modeling.…”
Section: Related Researchmentioning
confidence: 97%
“…The work by Permualla et al [4] has the best scaling of any individual level Epidemiology simulation known to the authors, and is based on previous EPISIMDEMICS work [1]. The system uses the same disease model and transmission function, but is based on a hierarchical social network construction similar to [12], a population of homogeneous agents, and lacks the ability to model interventions.…”
Section: Message Aggregationmentioning
confidence: 99%
“…The fastest known simulation [4] reported a speedup of 10,000 on 64K cores (15.2% efficiency) on Cray XT5. Our approach achieves a speedup of 14,357 (22% efficiency) on the same number of cores on Cray XE6.…”
Section: Introductionmentioning
confidence: 99%
“…There is a pre-defined travel time between any two locations. A reaction-diffusion model based on [20] has been employed to simulate the intralocation and inter-location spread of the disease. The reaction function determines the intra-location spread of disease.…”
Section: Experimental Analysismentioning
confidence: 99%